Genetically modified foods: A critical review of their promise and problems - Chen Zhang; Robert Wohlhueter; Han Zhang (Food Science and Human Wellness)
The term “genetic modified organisms (GMO)” has become a controversial topic as its benefits for both food producers and consumers are companied by potential biomedical risks and environmental side effects. Increasing concerns from the public about GMO, particularly in the form of genetic modified (GM) foods, are aimed at the short- and long-lasting health problems that may result from this advanced biotechnology. Complex studies are being carried out around the world independently to evaluate the advantages and disadvantages of GM foods. In this paper, we attempt to summarize up-to-date knowledge about the benefits and potential problems of GM food. We also introduce some recent technological developments in GM foods and their impact in the field.